Causes of Death Among Prostate Cancer Patients Aged 40 Years and Older in the United States - Ye, Yuzhong; Zheng, Yongqiang; Miao, Qi; Ruan, Hailong; Zhang, Xiaoping (Frontiers in Oncology, 2022)
Purpose Little is known about the detailed spectrum of the cause of death associated with prostate cancer (PCa). This study systematically characterized the cause of death among patients with PCa. Methods Patients aged 40 years and older with primary PCa were identified from the Surveillance, Epidemiology, and End Results program. Mortality rates were estimated. Standardized mortality ratios (SMRs) of non-cancer deaths were calculated to evaluate the risk of death and to compare with the cancer-free population. Results This study included 1,170,489 patients with PCa. There were 501,262 deaths, of which 27.4% were due to PCa and 57.0% were due to non-cancer causes. Non-cancer deaths increased over time from 1975 to 2016, and index cancer death decreased continually. The risk of non-cancer deaths was 1.45 times (SMR, 1.45; 95% confidence interval [CI], 1.45–1.46) that of the general population. Cardiovascular disease was the most common non-cancer cause of death, accounting for 30.2% of all deaths among PCa patients. Alzheimer’s disease (SMR, 3.92; 95% CI, 3.85–4.00) had the highest risk of death. The mortality rate and SMR of non-cancer deaths increased with increased follow-up after diagnosis. Conclusion Instead of the index cancer, non-cancer comorbidities were the leading cause of death among patients with PCa, and the risk of non-cancer deaths was much higher than among the general population. Clinicians and researchers should be aware of this trend to conduct timely and targeted interventions.